On the signal‐to‐noise ratio efficiency and slab‐banding artifacts in three‐dimensional multislab diffusion‐weighted echo‐planar imaging. Issue 2 (19th March 2014) - Engström, Mathias; Mårtensson, Magnus; Avventi, Enrico; Skare, Stefan
<x xml:space="preserve">Abstract</x> Purpose Three‐dimensional (3D) multislab diffusion‐weighted echo‐planar imaging (EPI) has been suggested as an alternative for high‐resolution diffusion‐weighted imaging. In this work, the key components of the sequence are investigated, optimal scan parameter settings suggested, and a signal‐to‐noise ratio (SNR) analysis, comparing 2D diffusion‐weighted EPI and 3D multislab diffusion‐weighted EPI, is performed. Methods Slab profiles were measured using 3D multislab EPI to investigate slab profile saturation effects with respect to TR, T1 and overlap between slabs. For short TR values, two methods to reduce the slab banding artifacts are proposed. Moreover, the SNR for 2D and 3D multislab (3D‐MS) DWI have been simulated for various anatomical coverages and slab thicknesses. Results Simulated 3D multislab scans were shown to be more SNR‐efficient than a corresponding 2D scan, for all investigated anatomical coverages and slab thicknesses. Slab banding artifacts being negligible for long repetition times (TRs) were strong for a TR of 2000 ms, proving that they stem from T1‐saturation effects. This banding was largely reduced by the suggested correction methods. Conclusion In the low TR regime, T1‐saturation effects between adjacent slabs need to be taken in consideration to avoid slab‐banding artifacts for multislab sequences. With the proposed correction methods the difference between the SNR‐optimal TR and the TR where slab‐banding artifacts become acceptable is reduced. Magn Reson Med 73:718–725, 2015. © 2014 Wiley Periodicals, Inc.